Liberty in Wordsworth’s Sonnets - Samad, Haybat Abdul (European Scientific Journal, ESJ, 2019)
Wordsworth once declared that for an hour thought given to poetry, he had given twelve to the state of society. However true this declaration might be, it helps to remind us that some of Wordsworth’s noblest verse and prose was inspired by political passion. The most prominent fact about Wordsworth’s politics is that he was a trueborn Englishman, and his roots struck deep into English soil. He was country-born and country-bred. Besides, he belonged by birth to the middle class. Thanks to this middle class, upbringing. A sense of moderation governed his course in life and kept him away from committing himself to any definite party throughout his life. Wordsworth reached maturity without meeting anyone who claimed priority on the account of rank. It is because of this moderate temper coupled with impatience of restrictions that Wordsworth’s mind seemed to be a productive soil for the revolutionary notions of Liberty, Equality and Fraternity. His interest in public affairs was motivated by the consequence of the American War as well as by the French Revolution. He had been too young, thoughtfully to consider the American War while it was going on. Therefore, when it ended, disbanded men began to return to the lakes. There he met some of these men and heard about others; and from what he saw and heard, he could conceive a horrible sense of war with all the suffering and evils it inflicts on the poor. On the other hand, in summer 1790, Wordsworth, accompanied by his friend Jones, set off for a walking tour in France and Switzerland – a tour that had significant consequences. Wordsworth landed at Calais on July 13th , 1790 – the eve of the day on which the king was to swear fidelity to the new constitution, and over-whelm people by a great tide of joy. In November 1791, Wordsworth went off again to France where he visited Paris, Orleans, and Blois in the main. In Blois, he made friendship with Michel Beaupy, a Republican officer in a mess of Royalists. The misery Beaupy witnessed among the extremely poor peasantry converted him not only to a Revolutionary citizen, but also to a patriot of the world. His heart was very much devoted to the cause of the common people and the poor. No other man, says Coleridge, had as great an influence upon Wordsworth as this benevolent and magnanimous patriot did.